The Via Negativa and the Aura of Words - Mortley, Raoul (Verbum Vitae, 2023)
The negative capacity is essential to creative thinking; we find it in the transcendentalism of the Judaeo-Christian tradition, though the Neoplatonist explanation of unknowing goes far further than simply pointing to the beyond; the idea of aura provides some understanding of how a word retains its influence even when negated; words or names are crucial in the move upwards in the mystical journey, and in the Neoplatonist and Christian tradition names or words are said to be fundamental, despite the via negativa; the linguistic ontology of Platonism underpins the existence of the names: but we do not have to believe in the ontic status of names for their aura to operate as we meditate over them.